The Effect of Current Ratio and Debt-to-Equity Ratio on Firm Value: The Moderating Role of Profitability in Transportation and Logistics Firms Listed on the Indonesia Stock Exchange (2020–2024) - Edi Suyitno; Rilla Gantino; Ratna Susanti (Indonesian Journal of Taxation and Accounting, 2026)
Purpose - This study aims to examine how liquidity, leverage, and profitability influence firm value in the transportation and logistics subsector listed on the Indonesia Stock Exchange (IDX), while also investigating the moderating role of profitability in shaping market responses to financial policies. The research is motivated by inconsistent empirical findings regarding the relationships between liquidity, capital structure, and firm value, particularly in asset-intensive industries that are sensitive to economic fluctuations. Methods - Using a quantitative explanatory design, the study analyzes secondary data obtained from publicly available financial statements and market information of transportation and logistics firms listed on the IDX during the 2020–2024 period. The unit of analysis is firm-year observations, with an initial dataset of 130 observations that was refined through screening and normalization procedures to 117 observations suitable for analysis. Hypotheses were tested using moderated regression analysis (MRA) estimated through pooled ordinary least squares. Findings - The results show that leverage, measured by the debt-to-equity ratio (DER), has a negative and statistically significant effect on firm value, while liquidity measured by the current ratio (CR) does not have a significant direct effect at the 5 percent level. Profitability, proxied by return on assets (ROA), shows a significant negative coefficient in the baseline model; however, interaction analysis reveals that profitability strengthens the relationship between liquidity and firm value and weakens the negative effect of leverage. These findings indicate that investors evaluate liquidity and financing decisions differently depending on the firm’s profitability condition. Research Implication - The study is limited by the use of pooled regression and by the reduced sample size after data screening. Nevertheless, the research contributes to corporate finance literature by integrating liquidity, leverage, and profitability within a moderated framework and provides managerial insights for improving financial policy decisions in capital-intensive industries. Originality - The research contributes to corporate finance literature by integrating liquidity, leverage, and profitability within a moderated framework